Climate Amenities and Adaptation to Climate Change: A Hedonic-Travel Cost Approach for Europe - Salvador Barrios; J. Nicolás Iba\~nez Rivas (Fondazione Eni Enrico Mattei (FEEM), 2014)
We investigate the impact of climatic change on welfare in European regions using a hedonic travel-cost framework and focusing on tourism demand. Our hedonic price estimations combine detailed hotel price information with tourism-specific travel cost estimations for each pair of EU region. This approach allows us to estimate different valuations of climate amenities depending on time duration of holidays. In our analysis of adaptation to climate change we therefore consider holiday duration as variable of adaptation. Our findings suggest that the rise in temperature in preferred destination choices during the summer season (i.e. southern EU) is likely to yield significant welfare losses. As a result European tourists are more likely to spend shorter (and more frequent) holidays and to diversify their destination choices in order to mitigate these losses.
Keywords: L8; Q5; 330; Climate Change; Hedonic Prices; Travel Cost; Tourism; Europe